Adaptation of MRF-PLL Method to be Utilized with Fixed Point Digital Signal Processors Under Unbalanced Input Voltage Conditions - Ozkilic, Mustafa Cem; Obdan, Atiye Hulya (GAZI UNIV, 2018)
Considering the pollution created by the fossil and nuclear type fuels during electrical energy production, utilization of renewable energy has been preferred and studies have accelerated in recent years. In grid connected renewable energy systems, the amplitude and the frequency of the fundamental voltage have to be tracked quickly and the system connected to the grid, even under grid disturbances, has to be adapted to the grid quickly. For this kind of adaptation, closed loop detection methods are used in order to gather the frequency and the amplitude information. By having this information, it would be possible to control the power factor, active and reactive power flow of the system The most frequent used adaptation method is phased locked loop (PLL) method. In this study, Synchronous Reference Frame (SRF) and Multiple Reference Frame (MRF) Phased Locked Loop (PLL) methods have been investigated and applications of SRF-PLL along with MRF-PLL with fixed point digital signal processors/microcontrollers by utilizing Matlab-Simulink simulation comparisons have been done.
Keywords: Phase locked loop (PLL); synchronous reference frame (SRF); multiple reference frame (MRF); grid connected system; three phase unbalanced system; PHASE; DESIGN; SYNCHRONIZATION; OPERATION; ALGORITHM; SYSTEM; Engineering